Analysis of Electronic Donations on the Revolution of Social Behavior in Charitable Interests in the Digital Era - Dinda Regina Rahman; Nahdatul Zahra; Syifa Awaliyah; Kholis Ridho (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
In the era of digital transformation, fundraising through donations is no longer limited to donation boxes or collections conducted by philanthropic organizations or similar social institutions. Currently, social organizations are leveraging digital platforms to sustain donation funds through online innovations. This allows us to contribute donations anytime and anywhere. This research aims to analyze the social behavior related to the interest in charitable giving through electronic donations. The research method used in this study is qualitative, with a questionnaire distributed to a maximum of 30 respondents interested in donating through electronic donations. The results of this study indicate a high level of interest in making ZIS payments digitally, as it is more practical and flexible to use.